Pengaruh Content Marketing, Price Discount, dan Online Customer Review Terhadap Impulse Buying Parfum ''Saff & Co'' Melalui Tiktok di Surabaya - Shila Radasahila; Ni Made Ida Pratiwi; Ayun Maduwinarti (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
The advancement of information technology has shifted marketing strategies from conventional to digital platforms, with TikTok emerging as a key driver of modern consumer behavior, including impulse buying. This phenomenon is evident in the local perfume industry, such as SAFF & Co, which has successfully captured a significant market share through strong content strategies. This study aims to analyze thej nfluence of Content Marketing, Price Discount, and Online Customer Review on Impulse Buying of SAFF & Co perfume via the TikTok application in Surabaya. A quantitative associative approach was employed, using an online questionnaire distributed to 100 TikTok users who have purchased the product. The data were analyzed using multiple linear regression. The results indicate that Content Marketing and Price Discount have a positive and significant effect on Impulse Buying, while Online Customer Review does not show a significant partial effect. However, simultaneously, all three variables positively and significantly influence Impulse Buying. These findings imply that businesses can stimulate consumer impulse purchases through effective content and discount strategies, while the role of customer reviews still requires optimization to strengthen their psychological impact on consumer purchasing decisions in social media environments.